The Effect of Leadership, Competence and Discipline on Police Performance in the Soppeng Police Station - Arif Efendi; Ansar Ansar; Nur Fattah (Economics and Digital Business Review, 2020)
This research was conducted at the Soppeng Police Station. The Population is all 200 Police officer, because of the large number, Slovin is used, the result is 67 respondent who are sampled with a margin of error set 10% or 0.10. Data collection methods used are direct interviews with parties involved with the problem being discussed and giving questionnaires to Police in accordance with the research conducted. Data analysis was performed using linear multiple regression analysis, T- test, F-test and the coefficient of determination (R2) test. The results of the analysis show that (1) leadership influences performance of the Police in the Soppeng District Police; (2) competence influences performance of the Police in the Soppeng District Police; (3) discipline that supports performance of the Police in Soppeng District Police; (4) leadership, competence, and discipline influence performance of the Police in the Soppeng District Police.